Navigating Faith in the Digital Age: A Behavioural Model of Religious Pilgrimage Among Urban Muslim Gen Z in Indonesia - Chandra Budhi Septyandi; Eko Susanto; Sherly Raka Siwi Putri Utomo; Mega Fitriani Adiwarna Prawira (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2026)
Religious pilgrimage among Indonesia's urban Muslim Generation Z is undergoing a notable transformation, shaped by their digital fluency, heightened historical awareness, and evolving religious consciousness. This study explores these dynamics by extending the Theory of Planned Behavior (TPB) with six contextual variables: religious commitment, historical literacy, scientific skepticism, perceived relevance, destination attractiveness, and digital social norms. Using a structured online survey conducted over six weeks in August-September 2025, data were gathered from 400 respondents. We applied Structural Equation Modeling (Partial Least Squares) to analyze the model. Results reveal that religious commitment, historical literacy, and perceived relevance are key drivers of favorable attitudes toward pilgrimage, while scientific skepticism introduces a countercurrent—highlighting this generation's demand for authenticity and intellectual engagement in spiritual practice. Notably, digitally embedded social norms strongly influence intention, reflecting the performative nature of religious expression in online networks. Attitude and intention were found to significantly shape actual travel behavior, aligning with TPB while revealing impulsive tendencies rooted in strong ideological beliefs. These findings offer fresh perspectives on youth religiosity, digital spirituality, and the socio-cultural fabric of Islamic tourism. For practitioners, the study provides actionable insights into designing experiences that are historically grounded, culturally resonant, and digitally relevant for Indonesia's emerging cohort of Muslim travelers.